2021
DOI: 10.1002/mco2.69
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of neutrophils in autoimmune‐associated disorders: effector, predictor, and therapeutic targets

Abstract: Neutrophils are essential components of the immune system and have vital roles in the pathogenesis of autoimmune disorders. As effector cells, neutrophils promote autoimmune disease by releasing cytokines and chemokines cascades that accompany inflammation, neutrophil extracellular traps (NETs) regulating immune responses through cell–cell interactions. More recent evidence has extended functions of neutrophils. Accumulating evidence implicated neutrophils contribute to tissue damage during a broad range of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“… 6 , 7 , 8 As the most abundant cells in innate immune cells, neutrophils also play an essential role in the occurrence and development of psoriasis. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 , 7 , 8 As the most abundant cells in innate immune cells, neutrophils also play an essential role in the occurrence and development of psoriasis. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] As the most abundant cells in innate immune cells, neutrophils also play an essential role in the occurrence and development of psoriasis. 9,10 The traditional defense mechanisms of neutrophils include pathogen phagocytosis, degranulation, and cytokine production. Studies have recently found that neutrophils can undergo a unique cell death process called "NETosis" when stimulated by inflammatory factors, chemicals, or metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the IL‐6R mAbs remarkably decreased ALT and AST levels in the serum (Figure 3C). Furthermore, to determine the inflammation of the lung tissue, we detected levels of myeloperoxidase (MPO), the sensitive biomarker associated with neutrophil accumulation‐mediated tissue injury in lung tissues 28,29 . The results suggested that MPO levels were significantly lowered in the h‐mIL‐6R mAb‐ and Tocilizumab‐treated SIRS mice (Figure 3D), suggesting that inflammation in lung tissue was lessened by the IL‐6R mAbs.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, to determine the inflammation of the lung tissue, we detected levels of myeloperoxidase (MPO), the sensitive biomarker associated with neutrophil accumulation-mediated tissue injury in lung tissues. 28,29 The results suggested that MPO levels were significantly lowered in the h-mIL-6R mAb-and Tocilizumab-treated SIRS mice (Figure 3D), suggesting that inflammation in lung tissue was lessened by the IL-6R mAbs. Given that kidney injury is frequently complicated with SIRS, we detected blood urea nitrogen (BUN) and creatinine levels to evaluate the alterations of the renal function in the murine SIRS model.…”
Section: The H-mil-6r Mab Alleviated Lps-induced Sirs In the Il6r-e(h...mentioning
confidence: 93%